THE DECISION ANALYSIS AND DEVELOPMENT OF WEB-BASED OPERATION DASHBOARD PRODUCTION USING SCRUM FRAMEWORK - Syaeful Anas Aklani (JURNAL INFORMATIKA DAN KOMPUTER, 2022)
With the rapid development of technology, information systems can be developed and used to help people obtain information more easily. One of the systems that are popularly used to present critical information is the operational dashboard which is commonly used in manufacturing industries. Manufacture itself means a process to convert raw materials into a product. It consists of a few processes, namely planning and choosing materials, as well as going through various machine processes that is known as a production line. In each of the production lines, there are line leaders to monitor line performances as well as identify and solve the problem that arises. However, without access to the real-time data of the line performance, it will be difficult to identify the problem and increase the probability of making the wrong choice and additional losses. For that reason, this research aims to analyze, design, and develop a web-based operational dashboard that displays generally used data. Using PHP, JavaScript, Bootstrap as well as SQL Server, the writer succeeded in developing a web-based operational dashboard that could help line leaders in accessing real-time production line data hence allowing them to make a better judgement.